Invalidated and ‘salty’: an auto/biographical and theoretical review of the lived experiences of individuals with PoTS - Marks, Harriet (Frontiers in Sociology, 2024)
Postural orthostatic Tachycardia Syndrome (PoTS), sometimes also written as ‘POTS’, is a form of dysautonomia (dysfunction of the autonomic nervous system) and orthostatic intolerance (which causes symptoms to be worsened when standing). This paper explores the extant literature on the lived experiences of those living with PoTS in relation to interactions between patients and healthcare providers as well as interactions at the level of the individual between PoTSies and those around them. My title contains the word ‘salty’ because it can be used to describe the feeling of being frustrated, while also reflecting a specific dietary change recommended to many (but not all) PoTS patients when they are told to consume additional sodium to minimise symptoms. COVID-19 is thought to have led to an increased prevalence of PoTS so this topic is particularly relevant to contemporary discussions and debates. In this sociological article, I refer not only to existing research on the lived experiences of having PoTS but also that of other chronic illnesses when relevant. The following themes are explored through auto/biographical and theoretical analysis: Undiagnosed and Invalidated; (In)Visible; Impacts of Diagnosis; Recovery and Expectations; Community. Reflecting auto/biographically, I have included analysis of interactions related to my lived experiences of presyncope, COVID-19 and dysautonomia, as I have been diagnosed with PoTS myself, which is thought to have been significantly exacerbated by the COVID-19 virus. This research is sociological, rather than medical or psychological, and conclusions are drawn about what is known so far about the lived experiences of living with PoTS, as well as discussion about what remains unknown, as there is currently a paucity of research on the lived experiences of individuals with PoTS and its comorbidities.